Improving outcomes in asthma by Commissioning Quality and Innovation (CQUIN). (24th May 2012) - Kamath, P; Roy, S; Dasgupta, S; Bose-Haider, B; Gorman, S; Tunstall, Y; Hoare, C; Leighton, K
Abstract : Background: Our catchment population has had higher than national average of asthma attendances to primary care and emergency department in this area of Northwest England. CQUIN payment framework enables commissioners to reward excellence, by linking a proportion of the healthcare providers income to the achievement of local quality improvement goals. Methodology: BTS annual children's asthma audit pre and post introduction of CQUIN (Commissioning Quality and Innovation) recommendations to reduce admission rates and maintain good control of their symptoms. Clinical Setting: 4 district general hospitals attached to Pennine Acute Trust with a catchment population of nearly 1 million. Results: Initial audit results in November 2009 identified suboptimal performance in asthma education, discharge planning and the early use of oral steroids. Following the CQUIN recommendations, an intervention team was formed to address the issues raised and a robust strategy was developed and the outcomes were evaluated by a repeat BTS audit in November 2010. Strategies included developing clear guidelines, seamless integrated care pathway from admission to discharge, robust education programme for all frontline medical and nursing personnel and enrolling nurses for diploma in asthma management to take on a more specialist role. The distribution of cases in relation to age, gender and severity was similar to the national cohort. These interventions resulted in good outcomes for a number of CQUIN indicators including more than 50% improvement in discharge planning, 50% reduction in CXR's and 3 fold reduction in the use of antibiotics for exacerbations. The results for oral steroids administration within an hour of diagnosis was well above national average. Conclusions: Focussed education to patients, parents and clinical personnel improves clinical outcomes. Integrated care pathway standardises care and improves patient experience. CQUIN schemes reward excellence and improve clinical outcomes.